The relationships between positive coping style, resilience, and illness stigma in patients with Meige syndrome: a cross-sectional study - Li, Meng; Li, Mengtian; Zhang, Ning; Zhou, Linghan; Zhang, Wenling; Yang, Kezhen; Yang, Xiaoyu; Li, Shen; Li, Yanhong; Liu, Feng; Li, Qiong; Wei, Junfan; et al. (Frontiers in Psychiatry, 2025)
ObjectivesThe present study aimed to investigate the levels of illness stigma in patients with Meige syndrome and to determine the association of socio-demographic characteristics, positive coping style, and resilience with illness stigma in patients with Meige syndrome.MethodA cross-sectional survey using convenience sampling was conducted in four hospitals in China from March 2025 to May 2025. A total of 280 patients clinically diagnosed with Meige syndrome were recruited. A socio-demographic characteristic questionnaire, the Chinese version of the Stigma Scale for Chronic Illness, the Chinese version of the simplified coping style questionnaire, and the Chinese version of the 10-item Connor–Davidson resilience scale were used to perform this research. Statistical analyses were performed using SPSS 27.0.ResultA high level of illness stigma was observed among 280 participants, as reflected by a mean score of 90.40 ± 25.59. The present study identified a negative correlation between illness stigma, positive coping style, and resilience. Multiple linear regression analysis showed that living arrangement (β = −0.16, p = 0.007), self-care ability (β = 0.13, p = 0.026), positive coping style (β = −0.15, p = 0.012), and resilience (β = −0.18, p = 0.002) were significant factors associated with illness stigma in Meige syndrome patients.ConclusionThis study reveals that patients with Meige syndrome experience high levels of illness stigma, which is associated with factors including living arrangement, self-care ability, positive coping style, and resilience. Healthcare professionals should prioritize stigma reduction in individuals with Meige syndrome, particularly those living alone or with limited self-care abilities, through targeted psychological support that enhances positive coping and resilience.